2013
DOI: 10.1177/1553350612471206
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Innovative, Cordless Ultrasonic Dissector

Abstract: Ultrasonic thermal energy is commonly used for dissection and vessel ligation. This study compared HARMONIC ACE and Sonicision Cordless Ultrasonic Dissector (SCUD). The devices were used in an in vivo porcine model to coagulate 189 arteries up to 5 mm. Seal times were similar: SCUD, 5.2 ± 1.7 s; ACE, 4.9 ± 1.5 s (P = .20). Burst pressures for SCUD and AVE were 578 ± 284 and 605 ± 288 mm Hg, respectively (P = .48). Stratification by vessel diameter yielded similar results. In all, 17 applications resulted in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 14 publications
0
29
1
Order By: Relevance
“…Apart from being cordless and allowing freedom of movement during surgery, the major advantage of the SCUD is the reduced cost compared to more high‐end endoscopic sealing devices. The SCUD performed similarly to the Harmonic ACE for vessel sealing times, burst pressures, collateral thermal damage, and seal failure rates in vivo in pigs . The SCUD had significantly decreased surgical smoke production compared to Harmonic ACE in ex vivo studies .…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Apart from being cordless and allowing freedom of movement during surgery, the major advantage of the SCUD is the reduced cost compared to more high‐end endoscopic sealing devices. The SCUD performed similarly to the Harmonic ACE for vessel sealing times, burst pressures, collateral thermal damage, and seal failure rates in vivo in pigs . The SCUD had significantly decreased surgical smoke production compared to Harmonic ACE in ex vivo studies .…”
Section: Introductionmentioning
confidence: 92%
“…Consequently, there is a demand for more economical laparoscopic vessel sealing solutions. Recently, the Sonicision (Covidien) cordless ultrasonic dissector (SCUD) was marketed . The SCUD is the first cordless energy‐based hemostatic device for laparoscopic tissue dissection and vessel sealing.…”
Section: Introductionmentioning
confidence: 99%
“…3,9 We saw no iatrogenic injury to proximal tissue when using the device. The visual obstruction from plume by these devices also varies.…”
Section: Discussionmentioning
confidence: 79%
“…An in vivo porcine animal model demonstrated promising results as to the effectiveness of this device in ligating vessels and dividing tissue with increased efficiency as compared with another commercially available ultrasonic dissector. 1 A second preclinical study focusing on the emissivity and temperature profile of the passive and active jaws of ultrasonic devices found that Sonicision improves tissues cutting by heating the active blade hotter as compared to other commercially available devices. 9 Finally, a summary of available studies regarding quantification of surgical plume which may obstruct visualization of the operating field in laparoscopic surgery has determined that Sonicision has a low rate of visualization obstruction (4.8%).…”
Section: Discussionmentioning
confidence: 99%